0842 Objective Sleep In The First 2 YEARS Of Life: Cross-sectional And Longitudinal Association With Vitamin D. (27th April 2018) - Deng, Y; Wang, G; Jiang, Y; Lin, Q; Zhu, L; Jiang, F
Abstract: Introduction: Sleep roblems are truly the giant of pediatric public health challenges and also a source of major concern to parents and professionals. precise and effective treatment for infant sleep problems is of great benefits. This is based on fully appreciation of the biopsychosocial contributing factors. Infant sleep problems could be resulted from biological factors, of which the role of vitamin D deficiency has been implicated in some clinical observation, but require further investigation. Methods: Data was from 262 infants of the Children Health Promote Project in Shanghai (CHPPS). The Infant sleep was measured with acti-watch at 6, 12, 18, and 24 months. Vitamin D status was assessed using electrochemiluminescence immunoassay in cord blood and vein blood at 2-year-old. Results: The prevalence of vitamin D deficiency in cord blood is 50.4% and 28% in 2-year-old toddlers. The mean night sleep duration at 6 months in the cord blood vitamin D deficiency group is 21.31 minutes (P=0.046) shorter than vitamin D non-deficiency group, while the total sleep duration at 24 months in the vitamin D deficiency is 27.38 minutes (P=0.041) shorter than the non-deficiency group at infant's 2-year-old. Positive association between vitamin D status in cord blood and night sleep duration, total sleep duration at 6-month-old has been found (β=0.201, p=0.017; β=0.176, p=0.044) but not found at the following time points in the first 2 years. Besides, cross-sectional relationship between both night sleep duration, total sleep duration and vitamin D status was confirmed at 2 years old (β=0.242, p=0.035; β=0.238, p=0.042). Conclusion: Infant objective-measured sleep exhibit a cliff change during the first year of life and turn to be mild stable at the following years. Vitamin D status has a temporal effect on promoting infant's sleep at the age of 2. The longitudinal effect of vitamin D status in cord blood seems to be short-lasting. Support (If Any): Chinese National Natural Science Foundation(81422040); MOE New Century Excellent Talents(NCET-13–0362); Ministry of Science and Technology(2016YFC1305203); Shanghai Science and Technology Commission(17XD1402800, 14441904004); Shanghai Jiao Tong University(YG2016ZD04).